2020
DOI: 10.1136/bmjopen-2019-034802
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported disability in relation to mortality in rural Malawi: a longitudinal study of over 16 000 adults

Abstract: ObjectivesWe investigated whether self-reported disability was associated with mortality in adults in rural Malawi.SettingKaronga Health and Demographic Surveillance Site (HDSS), Northern Malawi.ParticipantsAll adults aged 18 and over residing in the HDSS were eligible to participate. During annual censuses in 2014 and 2015, participants were asked if they experienced difficulty in any of six functional domains and were classified as having disabilities if they reported ‘a lot of difficulty’ or ‘can’t do at al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…53 A Malawian study reported that mortality rates from HIV were higher among people with disabilities, although without statistical significance. 54 Health system failures will make 95:95:95 targets hard to reach There are important negative consequences of these health systems failures for individuals, aside from the impact on mortality. People living with HIV and disabilities frequently experience worse quality of life, educational and social exclusion, and poorer mental health compared to those living with HIV alone.…”
Section: Hiv Service Access By People With Disabilitiesmentioning
confidence: 99%
“…53 A Malawian study reported that mortality rates from HIV were higher among people with disabilities, although without statistical significance. 54 Health system failures will make 95:95:95 targets hard to reach There are important negative consequences of these health systems failures for individuals, aside from the impact on mortality. People living with HIV and disabilities frequently experience worse quality of life, educational and social exclusion, and poorer mental health compared to those living with HIV alone.…”
Section: Hiv Service Access By People With Disabilitiesmentioning
confidence: 99%
“… 6 Thus far, only a few studies have investigated life expectancy among working-age adults with disability, and these have found increased risk for mortality. 5 , 14 , 15 , 16 , 17 However, apart from a Swedish study on young adults with mild intellectual disability, these studies were conducted in countries without a universal welfare-state model. Thus, inferring these findings to European welfare states may not be valid.…”
Section: Introductionmentioning
confidence: 99%